Outcomes after Bronchoscopic Procedures for Primary Tracheobronchial Amyloidosis: Retrospective Study of 6 Cases - Alloubi, Ihsan; Thumerel, Matthieu; Bégueret, Hugues; Baste, Jean-Marc; Velly, Jean-François; Jougon, Jacques (Pulmonary Medicine, 2012)
Respiratory amyloidosis is a rare disease which refers to localized aberrant extracellular protein deposits within the airways. Tracheobronchial amyloidosis (TBA) refers to the deposition of localized amyloid deposits within the upper airways. Treatments have historically focused on bronchoscopic techniques including debridement, laser ablation, balloon dilation, and stent placement. We present the outcomes after rigid bronchoscopy to remove the amyloid protein causing the airway obstruction in 6 cases of tracheobronchial amyloidosis. This is the first report of primary diffuse tracheobronchial amyloidosis in our department; clinical features, in addition to therapy in the treatment of TBA, are reviewed. This paper shows that, in patients with TBA causing airway obstruction, excellent results can be obtained with rigid bronchoscopy and stenting of the obstructing lesion.